Tail Risk Around FOMC Announcements - Jacobs, Kris; Ke, Sai; Pan, Xuhui (Nick) (Journal of Financial and Quantitative Analysis, 2026)
Abstract Predictive regressions of market returns on option-implied moments measured before pre-scheduled FOMC meetings show that tail risks play an important role in understanding the market risk premium around FOMC announcement days. Skewness and kurtosis, which capture investors’ expectations of the tails of the return distribution, robustly predict post-FOMC returns both in-sample and out-of-sample. The predictability lasts up to 1 week and is stronger for expansionary monetary policy shocks. The signs of the corresponding risk premiums are consistent with economic intuition, illustrating the role of periods with high risk premiums to confirm theoretical predictions.